Peripheral Neuropathy in Pregnant Women with Iron Deficiency Anemia: A Cross-Sectional Analytical Study: Peripheral Neuropathy in Pregnant Women with Iron Deficiency Anemia - Amil, Javaria; Shafiq, Muhammad Bilal Ahmad; Zubair, Muhammad; Batool, Tehreem; Zahoor, Ayesha; Asghar, Sadia; Jamil, Bushra (Pakistan Journal of Health Sciences, 2026)
Pakistan faces a high burden of nutritional anemias, with iron-deficiency anemia being the most prevalent. Imbalanced iron levels had a central role in neuropathies. Objectives: To assess the prevalence of peripheral neuropathy in pregnant women having Iron deficiency anemia through associated clinical and laboratory Parameters. Method: A cross-sectional analytical study was done at the Department of Obstetrics and Gynecology and the Clinical Neurophysiology Unit of Niazi Welfare Foundation Teaching Hospital, Sargodha, from July 1st, 2025 to November 30, 2025. A sample of 350 women was targeted using consecutive sampling. Both sensory and motor nerve conduction parameters of the lower limbs and upper limbs were evaluated. Data were analyzed using SPSS version 26. Chi-square tests assessed associations between anemia severity (mild: Hb 10–10.9 g/dL; moderate: 8–9.9 g/dL; severe: <8 g/dL) and peripheral neuropathy at significance level of p-value <0.050. Results: Out of 350 pregnant women, anemia was mild in 98 (28.0%), moderate in 164 (46.9%). Peripheral neuropathy was revealed in 102 women (29.1%,) Neuropathic symptoms involving numbness was revealed in 42.1%, tingling (paresthesia) in 38.7%, burning sensations in 35.5%, & reduced ankle reflexes in 27.4%. This study found a significant association between anemia severity and neuropathy frequency (χ² = 42.9, p<0.001), showing a marked increase in neuropathy prevalence with worsening anemia. Conclusions: Study reported that iron-deficiency anemia is associated with the onset and progression of peripheral neuropathy. These observations suggest that evaluation for iron deficiency should be routinely included when assessing patients presenting with peripheral neuropathy.